Efficacy of iron supplementation on fatigue and physical capacity in non-anaemic iron-deficient adults: a systematic review of randomised controlled trials. Issue 4 (5th April 2018) - Houston, Brett L; Hurrie, Daryl; Graham, Jeff; Perija, Brittany; Rimmer, Emily; Rabbani, Rasheda; Bernstein, Charles N; Turgeon, Alexis F; Fergusson, Dean A; Houston, Donald S; Abou-Setta, Ahmed M; Zarychanski, Ryan
Abstract : Objective: Iron supplementation in iron-deficiency anaemia is standard practice, but the benefits of iron supplementation in iron-deficient non-anaemic (IDNA) individuals remains controversial. Our objective is to identify the effects of iron therapy on fatigue and physical capacity in IDNA adults. Design: Systematic review and meta-analysis of randomised controlled trials (RCTs). Setting: Primary care. Participants: Adults (≥18 years) who were iron deficient but non-anaemic. Interventions: Oral, intramuscular or intravenous iron supplementation; all therapy doses, frequencies and durations were included. Comparators: Placebo or active therapy. Results: We identified RCTs in Medline, Embase, Cochrane Central Register of Controlled Trials, Cumulative Index of Nursing and Allied Health, SportDiscus and CAB Abstracts from inception to 31 October 2016. We searched the WHO's International Clinical Trials Registry Platform for relevant ongoing trials and performed forward searches of included trials and relevant reviews in Web of Science. We assessed internal validity of included trials using the Cochrane Risk of Bias tool and the external validity using the Grading of Recommendations Assessment, Development and Evaluation methodology. From 11 580 citations, we included 18 unique trials and 2 companion papers enrolling 1170 patients. Using a Mantel-Haenszel random-effects model, iron supplementation was associated with reduced self-reported fatigue (standardised mean difference (SMD) −0.38; 95% CI −0.52 to −0.23; I 2 0%; 4 trials; 714 participants) but was not associated with differences in objective measures of physical capacity, including maximal oxygen consumption (SMD 0.11; 95% CI −0.15 to 0.37; I 2 0%; 9 trials; 235 participants) and timed methods of exercise testing. Iron supplementation significantly increased serum haemoglobin concentration (MD 4.01 g/L; 95% CI 1.22 to 6.81; I 2 48%; 12 trials; 298 participants) and serum ferritin (MD 9.23 µmol/L; 95% CI 6.48 to 11.97; I 2 58%; 14 trials; 616 participants). Conclusion: In IDNA adults, iron supplementation is associated with reduced subjective measures of fatigue but not with objective improvements in physical capacity. Given the global prevalence of both iron deficiency and fatigue, patients and practitioners could consider consumption of iron-rich foods or iron supplementation to improve symptoms of fatigue in the absence of documented anaemia. PROSPERO registration number: CRD42014007085 .